(untitled) (Global Journal of Human-Social Science, 2012)
Human development paradigm is one of the emerging development models which is widely accepted all over the world This paper tries to shed light on the methodology applied by Nepal for calculating GDI and GEM and it also focuses on the trend and pattern of GDI and GEM in Nepal The primary objective of this study is to examine the change in pattern of GDI and GEM of Nepal over the last 10 years from 1996 to 2006 This study is based on the secondary source of information collected from the Nepal Human Development Reports NHDR 1998 to 2009A D The study indicates that desegregation of GDI and GEM at sub national levels has enormous differences in terms of human development especially from gender perspective The level of both GDI and GEM has increased over the time the value of GDI has improved from 0 267 in 1996 to 0 499 in 2006 Likewise the value of GEM has also increased form 0 191 in 1996 to 0 496 in 2006 but still it has not reached in satisfactory level particularly while comparing the status of these two indicators in development regions there is wide gap This study can be effective for policy intervention and further planning for women empowerment